Assaulted caramel - Flower, Amanda (Thorndike, Maine : Center Point Large Print, 2018)
"When Bailey King hears her grandfather's heart condition has worsened, she rushes to Harvest, Ohio, where her grandparents still run Swissmen Sweets, the Amish candy shop. She finds her grandfather is doing better than she feared, she also finds a local Englisch developer dead in the candy shop kitchen--with her grandfather's chocolate knife buried in his chest"--
Originally published: Kensington Publishing Corp.
Includes recipe.
Keywords: Confectioners -- Fiction; Amish -- Fiction; Murder -- Investigation -- Fiction; Large type books; Amish; Confectioners; Large type books; Murder -- Investigation; Detective and mystery fiction; Religious fiction; Detective and mystery fiction; Fiction; Religious fiction; Mystery fiction; Christian fiction; Detective and mystery fiction; Religious fiction